2014 8th Conference of the European Study Group on Cardiovascular Oscillations (ESGCO) 2014
DOI: 10.1109/esgco.2014.6847566
|View full text |Cite
|
Sign up to set email alerts
|

Fractal behavior of heart rate variability during ECG stress test in cardiac patients

Abstract: Linear measures of heart rate variability (HRV) during ECG stress test has been widely questioned due to the high signal non-stationary. Such limitations can be overcome by nonlinear measures of HRV based on typical properties of chaotic systems and deterministic fractal. Very few paper addressed such issue and aim of the paper is to describe fractal behavior of HRV during exercise. A fractal analysis by Higuchi's algorithm (FD) has been performed on 26 cardiac patients during resting, stress, early and late r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…D’Addio et al 19. performed fractal analysis on cardiac patients during resting, stress, early and late recovery phases of ECG stress test.…”
mentioning
confidence: 99%
“…D’Addio et al 19. performed fractal analysis on cardiac patients during resting, stress, early and late recovery phases of ECG stress test.…”
mentioning
confidence: 99%
“…They explain that the model works well even when it has been tested with data that the model has not been trained by them. In [55], the fractal dimension of ECG signal in OSAS (Obstructive Sleep Apnea Syndrome) patients has been studied. It is reported that normal breathing epochs can be discriminated from abnormal ones with fractal dimension.…”
Section: Methods To Classify Ecg Signals Into Different Disease Categoriesmentioning
confidence: 99%
“…HFD and Katz were measured on wavelet sub-band for detecting voice pathology [8]. HFD was also utilized to identify heart rate variability (HRV) on a cardiac patient ECG stress test [9]. HFD measurement depends on the value of the specified maximum time interval kmax.…”
Section: Introductionmentioning
confidence: 99%
“…HFD measurement depends on the value of the specified maximum time interval kmax. In previous studies, HFD was commonly measured at only one particular value of kmax [7]- [9]. Some researchers tried to analyze the HFD value in a range of kmax to obtain an optimum HFD value [10].…”
Section: Introductionmentioning
confidence: 99%